The Impact of the International Economic Crisis on Child Poverty in South Africa. Issue 2 (June 2015) - Maisonnave, Helene; Chitiga, Margaret; Decaluwé, Bernard; Mabugu, Ramos; Robichaud, Véronique; Shepherd, Debra; Van der Berg, Servaas; Von Fintel, Dieter
<x xml:space="preserve">Abstract</x> This article provides insights into the magnitude of the shocks associated with the recent global economic crisis in South Africa, and the extent of fragility in terms of poverty levels and, particularly, child well‐being. The analysis combines macro‐economic and micro‐economic tools and shows that the impact of the economic crisis was not severe on children's poverty headcount, but that material welfare declined across large parts of the distribution. The latter impact on welfare exacerbates poverty depth, moving the already poor further below the poverty line where they remain for much longer. This suggests that the major impact of the economic crisis was on the poorest, and that this is the most difficult to overcome.